2020
DOI: 10.5812/ircmj.102425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Delayed Admission to Intensive Care Units from the Emergency Department on the Mortality of Critically Ill Patients

Abstract: Background: Increasing in emergency department need to critical care, the number of intensive care unit bed worldwide is inadequate to meet these applies. Objectives: The aim of this study was to investigate the effect of waiting for admission to the Intensive Care Unit (ICU) in the Emergency Department (ED) on the length of stay in the ICU and the mortality of critically ill patients. Methods: This retrospective cohort study carried out between January 2012 - 2019 patients admitted to the ICU of a training an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Thirty-three of these were included in the MA (Table 3) [25][26][27][28][29][30][31][32][33][34][35][36][38][39][40][41][42][43][44][45][46][47][48][49][50][57][58][59][60][61]63,68,71]. The remaining 17 studies [3,9,37,[51][52][53][54][55][56]62,[64][65][66][67]69,70,72] were excluded for one of the following reasons:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-three of these were included in the MA (Table 3) [25][26][27][28][29][30][31][32][33][34][35][36][38][39][40][41][42][43][44][45][46][47][48][49][50][57][58][59][60][61]63,68,71]. The remaining 17 studies [3,9,37,[51][52][53][54][55][56]62,[64][65][66][67]69,70,72] were excluded for one of the following reasons:…”
Section: Resultsmentioning
confidence: 99%
“…(1) the specific EDLOS cut-off was not defined [3,9,37,[51][52][53][54]56,62,[64][65][66][67]69,72]; (2) one study reported data in severely ill mechanically ventilated patients [54]; and (3) raw data were missing in one study [70]. We subsequently acquired the original databases for four studies [34,41,42,45], which allowed us to perform analysis of nine different EDLOS cut-off values: 1.2 h [34,41,42,45,50], 1.5 h [34,[40][41][42]45], 2 h [32,34,41,42,45], 3 h [34,41,42,45,47,68], 4 h [33,[40][41][42]44,57,58], 5 h…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies conducted in Brazil, Taiwan, United Kingdom, Turkey, and other systematic reviews and meta-analysis also showed a similar association between ICU mortality and delayed admissions. [20][21][22][23][24] Patients with a Glasgow Coma Scale (GCS) score of less than 8 had an approximately fourfold higher likelihood of ICU mortality compared with patients with a GCS score of greater than or equal to 13 (adjusted odds ratio = 3.9732, 95% confidence interval: 2.1249-7.4290). Similar associations between GCS and ICU mortality were also observed in studies conducted in USA, Kenya, and Ethiopia.…”
Section: Discussionmentioning
confidence: 99%